Postmarketing surveillance: practical experience with ketotifen. Issue 6421 (24th March 1984) - Maclay, W P; Crowder, D; Spiro, S; Turner, P
Abstract : In a postmarketing surveillance of ketotifen (Zaditen), an oral preparation for the prophylaxis of bronchial asthma, 8291 patients completed records every three months for one year. The objectives were to record adverse events and efficacy and to communicate appropriate information to participating doctors and regulatory authorities. The patients recruited appeared to represent a typical cross section of patients with asthma in the United Kingdom. By subjective assessment 70% of patients found the medication efficacious. There were no unexpected or unacceptable side effects and those found were similar to those reported in clinical trials of ketotifen. Though this exercise showed that the pharmaceutical industry, regulatory authorities, and prescribing doctors were able to collaborate, the major outcome of the survey was already known. It remains to be seen whether this type of survey is of value in the continuing search for control and safety in prescribing.